Proyecto: control de las pudriciones radicales del frijol comun (Phaseolus vulgaris L.) en la zona andina - Valladolid, A.; Chumbiauca, L.; Munive, J.; Cantoral, E.; Esteves, C.; Peralta, E.; Minchala, L.; Defaz, M.; Rivadeneira, C.; Quiton, N.; Pastor Corrales, Marcial A.; Kornegay, Julia L. (International Center for Tropical Agriculture, 1991)
This project aims at: (1) identifying the major pathogens of the bean root rot complex, (2) screening for resistant germplasm, and (3) evaluating low-input control methods that will significantly decrease economic losses caused by root rots in the main bean producing regions of Peru, Ecuador, and Bolivia. The duration of the project is 3 yr as of June 1991 and the Swiss Development Cooperation (SDC) will fund it through the Bean Program for the Andean Zone (PROFRIZA-CIAT) and the contribution of the national research programs. Researchers from the 3 national programs will participate, with the scientific support of the plant pathology and breeding sections of CIAT's Bean Program. (AS-CIAT)